2012
DOI: 10.5999/aps.2012.39.4.338
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Analysis of Cranial Molding Therapy in Nonsynostotic Plagiocephaly

Abstract: BackgroundIt is known that nonsynostotic plagiocephaly does not spontaneously improve, and the craniofacial deformities that result from it. This study was conducted to analyze the effectiveness of helmet therapy for the nonsynostotic plagiocephaly patient, and to suggest a new treatment strategy based on this analysis.MethodsA total of 108 pediatric patients who had undergone helmet therapy after being diagnosed with nonsynostotic plagiocephaly were included in this study. The patients were classified accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 28 publications
2
33
0
Order By: Relevance
“…Reviewing 159 infants, Graham et al [13] found that patients who started helmet therapy at >8 months of age had larger final TDD with less relative improvement than patients who started helmet therapy at <8 months despite similar initial TDD. In a study consisting of 108 patients, Yoo et al [9] calculated that the rate of successful treatment (TDD ≤ 5 mm) significantly decreased when the age at therapy initiation was >9.1 months. In 116 patients who underwent laser measurement, Thompson et al [14] noted that patients who started therapy at 4-8 months had superior outcomes compared to those who started at <4 or >8 months.…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing 159 infants, Graham et al [13] found that patients who started helmet therapy at >8 months of age had larger final TDD with less relative improvement than patients who started helmet therapy at <8 months despite similar initial TDD. In a study consisting of 108 patients, Yoo et al [9] calculated that the rate of successful treatment (TDD ≤ 5 mm) significantly decreased when the age at therapy initiation was >9.1 months. In 116 patients who underwent laser measurement, Thompson et al [14] noted that patients who started therapy at 4-8 months had superior outcomes compared to those who started at <4 or >8 months.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic effects can be accomplished by inducing prominent areas to be retained passively and flattened areas to grow rapidly into the hollow space in the helmet 21 . Infants with deformational plagiocephaly were treated on the basis of a cranial vault asymmetry cutoff value of 10 mm 22 . According to the helmet therapy protocol, caregivers were told to keep the child in the helmet as much as possible, with greater than 23 hours of daily use recommended.…”
Section: Methodsmentioning
confidence: 99%
“…After the initial helmet fitting, the infants were followed every 2 to 4 weeks to adjust for both head growth and skull shape changes. Helmet therapy was discontinued when cranial vault asymmetry was less than 6 mm, 22 the cranial vault asymmetry index was less than 3.5%, 23 or no further helmet adjustment was possible because of cranial growth.…”
Section: Methodsmentioning
confidence: 99%
“…Prolonged time with the head rotated to one side can impact reflex patterns, muscle tone, and movement for later function. In addition, severe head turn preferences may promote asymmetric movements in early infancy [8,9] and lead to future complications in posture [1012]. Postural asymmetries, including infantile postural scoliosis, torticollis, and an asymmetrical skull shape including deformational plagiocephaly also result from prolonged head turn preference [1317].…”
mentioning
confidence: 99%